2005
DOI: 10.1108/02634500510603456
|View full text |Cite
|
Sign up to set email alerts
|

Price as a variable in online consumer trade‐offs

Abstract: PurposeTo determine the impact of price on consumer decision making in online environments.Design/methodology/approachUses a conjoint experiment to investigate the trade‐offs customers make when choosing and to establish their relative weights in online and offline situations.FindingsFinds that customers expect prices to be lower in an online environment than in a traditional sales channel.Research limitations/implicationsDespite acknowledged limitations of experimental design and student samples, the findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…The positive relationship between equity and satisfaction was supported in the literature (Oliver, 1993;Oliver & Swan, 1989a, 1989b. However, customers expect prices to be lower in an online store than in a traditional sales channel (Karlsson, Kuttainen, Pitt, & Spyropoulou, 2005). They may expect to get more value from an online store than from a physical store.…”
Section: Perceived Value and Satisfactionsupporting
confidence: 58%
“…The positive relationship between equity and satisfaction was supported in the literature (Oliver, 1993;Oliver & Swan, 1989a, 1989b. However, customers expect prices to be lower in an online store than in a traditional sales channel (Karlsson, Kuttainen, Pitt, & Spyropoulou, 2005). They may expect to get more value from an online store than from a physical store.…”
Section: Perceived Value and Satisfactionsupporting
confidence: 58%
“…Hubungan di antara keduanya telah dipelajari selama bertahun-tahun. Karlsson, Kuttainen, Pitt, & Spyropoulou (2005) dalam penelitiannya menemukan bahwa konsumen bersedia melakukan upaya untuk membeli secara online untuk mendapatkan penghematan harga. Hal Ini mungkin diimbangi oleh fakta bahwa internet dapat mengurangi biaya pencarian (waktu dan usaha) sebelum membeli.…”
Section: Keterkaitan Price Dengan Intensi Pembelian Kosmetik Halalunclassified
“…Jayawardhena et al (2007) found that “discerning” internet users were prepared to comparison shop using the internet to find the best prices. Karlsson et al (2005) noted that consumers are willing to make an effort to purchase online in order to make price savings, and that prices are expected to be lower online consequently price is a major motivation to shop online. Joines et al (2003) noted that it is the dual motivations of convenience and fast price search that allows consumers to search for the best offers more efficiently online, that is a strong motivation to shop online.…”
Section: Literature Reviewmentioning
confidence: 99%